Processo administrativo fiscal previdenciário - Berman, Vanessa Carla Vidutto (2008)
The object of the present work consists of the analysis of the administrative activities carried out by the collections of taxes allocated for the Social Security Funding. We aim at tracking a parallelism between the guaranties of the participants previewed in the entire legal framework and the administration prerogatives, covering as much the phase that precedes the entry as the one that is developed at a later date with the fiscal administrative process brought to action. The study begins with a brief covering of the origin and development of the State Power, going through all the historical moments; from the distinguished interventionism of the 18th century to the liberalism excess at the end of the same century, reaching the current model where the state maintains itself participative in the social relations, without being a centralizer of the economic activities nor a limiter of rights and private interests. Then, we dedicated to the general theory of the administrative process, including them in the applicable ruling; dealing with the principles applicable and bringing to light all the relevant legislation to the theme, with emphasis on the new structure arising from the emergence of Federal Revenue of Brazil, under the approach given by Law of 11.457/07 and according with the new statute applicable to the social security fiscal administrative process, inserted in Decree 70.235/72. In this topic we aimed at emphasizing the alterations suffered due to the new legal ruling brought to action. This dissertation has its main focus on the recognition that only through the administrative process carried out according to the democratic ruling in which we currently stand; hence the state activity will be able to act lawfully